La difusión de las cofradías marianas en el arzobispado de México, 1680-1750 - Salvador, Rodolfo Aguirre (Cauriensia, 2023)
The presente work analyzes the impulse that the brotherhoods of the archbishopric of Mexico gave to the cult of the Virgin Mary, between 1680 and 1750. Based on the consultation of the documents of the ecclesiastical subsidy in America, established by Felipe V, and of the pastoral visits, the devotions of the parishioners of the archbishopric are studied. The presence of Marian brotherhoods in parishes and convents shows their popularity and the triumph of those who promoted devotion. Undoubtedly, the different communities of the faithful found in the cult of the Virgin the answer to different needs. In addition, the Catholic reform proposed by the Council of Trent took good advantage of the impulse of these brotherhoods to strengthen the religiosity of the faithful and bring them closer to Christian worship.